Combined mild hypoxia and bone marrow mesenchymal stem cells improve expansion and HOXB4 gene expression of human cord blood CD34+ stem cells - Mohammadali, Fatemeh; Abroun, Saeid; Atashi, Amir (Archives of Biological Sciences, 2018)
Paper description: Expansion modalities of hematopoietic stem cells have been performed with the ultimate goal of improving engraftment of cord blood Expansion in culture remains a challenge because of our limited knowledge of factors that drive self-renewal beside expansion. Combining bone marrow mesenchymal stem cells and mild hypoxia (5% O2 tension) in serum-free culture not only improves expansion but can also significantly enhance self-renewal of hematopoietic stem cells. Our findings contribute to the development of more efficient culture systems for the ex vivo expansion of cord blood hematopoietic stem cells for cellular therapy. Abstract: Cord blood (CB) is a rich source of hematopoietic stem cells (HSC). It has been used successfully to treat a variety of hematological and non-hematological disorders. Beside the advantages of CB, its main disadvantages are the limited number of stem cells available for transplantation and delayed engraftment. Identifying strategies to enhance expansion and self-renewal of HSCs can improve transplantation efficiency. The aim of this study was to examine different culture conditions on ex vivo expansion and homeobox protein Hox-B4 gene (HOXB4) expression in cord blood CD34+ stem cells. Human cord blood CD34+ HSC were cultured in serum-free medium supplemented with cytokines with and without a feeder layer in normoxia (21% O2) and mild hypoxia (5% O2).At the end of 7 days of culture, the highest number of total nucleated cells (TNC), CD34+ cells, colony forming units (CFUs) and HOXB4 mRNA were observed in a co-culture of HSC with a bone marrow mesenchymal stem cell(MSC) feeder layer at 5% O2.We concluded that the combination of bone marrow (BM)-MSC and mild hypoxia (5% O2) not only improved HSC expansion but also enhanced HOXB4 gene expression as a self-renewal marker of HSC, and better mimicked the niche microenvironment conditions. https://doi.org/10.2298/ABS171028003M Received: October 28, 2017; Revised: December 21, 2017; Accepted: January 14, 2018; Published online: January 26, 2018 How to cite this article: Mohammadali F, Abroun S, Atashi A. Combined mild hypoxia and bone marrow mesenchymal stem cells improve expansion and HoxB4 gene expression of human cord blood CD34+ stem cells. Arch Biol Sci. 2018;70(3):…